Agentes antimicrobianos naturales de origen vegetal usados en la conservación de frutas y hortalizas - Colcha Lopez, Luis Fernando (2021)
ABSTRACT: Today, the consumption of fresh or minimally processed products has caused the need to look for new alternatives of natural origin since most of these processes are carried out through the use of chemical agents, which may be associated with diseases or problems in long-term health due to the consumption of these products, that is why bibliographic review aims to carry out an investigation on the main antimicrobial agents of plant origin used for the disinfection of fruits and vegetables, this search was carried out through a systematic review, such information was obtained from scientific articles that are related to the disinfection of minimally processed foods (fruits and vegetables), this process was carried out by using the PRISMA method for the inclusion and exclusion of information, taking into account the different variables that contribute to the review, obtaining as a result articles of great importance from which it was evidenced that essential oils are the most used ones, being the essential oil of oregano the microbicidal agent used in the proposal of two protocols for the disinfection of tomatoes at a concentration of 100ppm and for carrots at 250ppm, reaching the conclusion that among the antimicrobials of plant origin the compounds thymol and carvacrol are the main components with microbicidal effect that help to inhibit pathogenic microorganisms, such as E. coli, Salmonella and Listeria monocytogenes, the same ones that cause diseases by eating contaminated fruits and vegetables